Improving Critical Thinking Skills Using Animated Videos Based on Problem-Based Learning - Nevitaningrum Taningrum; Erwin Setyo Kriswanto; Aris Fajar Pambudi; Wahyu Dwi Yulianto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The materials related to football game tactics and strategies are mostly explained and taught in conventional theory. Students stated that learning tactics and strategy in soccer games is complicated and therefore difficult to understand because it uses conventional methods. Current developments have resulted in the acceleration of technology for learning in various conditions. This study aims to determine the learning outcomes of the twelfth grade students in senior high school by using animated videos based on problem-based learning in learning football games, especially in materials related to defensive patterns, attacking patterns, and football game formations. The method used in this study was experimental research using one group pre-test post-test design consists of 32 twelfth grade students (Male:12; Female:20). The learning process was evaluated using Formative Class Evaluation, and critical thinking skills were measured using critical thinking test instruments, The critical thinking assessment tool was evaluated by 4 experts. Result:This study showed significant differences in students’ critical thinking skills before and after applying problem-based learning animated videos [t=6.442; p= 0.000 (<0.05), with an increase of 14.65%. The achievement of student learning outcomes before implementing problem-based learning animated videos scored 66.66 in the poor category. After implementing problem-based learning animated videos, the score increased to 76.41 in the good category. Conclusion The application of animated videos based on problem-based learning in teaching and learning process helps students to theoretically understand football games with its complex tactics and strategies and to fully integrate their knowledge of defensive patterns, attacking patterns and formations in football games. Animated videos based on problem-based learning can provide stimuli that can encourage students to think analytically to improve their critical thinking and keep up with rapid technological developments.